EFEKTIVITAS PENGGUNAAN TOKEN ECONOMY DALAM MENINGKATKAN KEMAMPUAN KONTAK MATA PADA ANAK AUTISME DI SLB AUTISMA MUTIARA BANGSA PRATAMA (Single Subject Research di SLB Autisma Mutiara Bangsa Pratama) - Riski Hidayat; Arisul Mahdi (Jurnal Penelitian Pendidikan Khusus, 2023)
The research analyzed was based on the problems found in the Autisma Mutiara Bangsa Pratama SLB in the city of Padang. The result of the problem found is that there are children with ASD (Autism Spectrum Disorder) with impaired eye contact, where the child cannot make eye contact, making the learning process less effective. This study aims to improve the ability to make eye contact in children with ASD (Autism Spectrum Disorder) using the token economy technique. This research uses the SSR (single-subject research) method with an A-B-A design. in the A-B-A design, there are three conditions, namely baseline (A1), Intervention conditions (B). and baseline (A2). Data collection techniques are in the form of observation, interviews, and assessments. The data collection tool in this study uses a format in the form of an observation instrument in the form of a frequency instrument. Based on the results of the research that has been carried out and the explanation that has been presented in its entirety, it shows that the ability to make eye contact in children with ASD (Autism Spectrum Disorder) increases after being given the token economy technique treatment. So it can be concluded that the token economy technique is effective in increasing the eye contact ability of children with ASD (Autism Spectrum Disorder).Â Â